Willingness-to-pay value of cultural heritage and its management for sustainable conservation of George Town, world heritage site / Noor Fazamimah Mohd Ariffin - Noor Fazamimah, Mohd Ariffin (2015)
This research explores the issue of the local management system governing the heritage conservation in Malaysia which has not clearly defined the value of the cultural heritage in order to justify any benefits of preserving the cultural heritage as a tourism product for the sustainable heritage site conservation. There are conflicts between stakeholders relating to the benefits of the UNESCO World Heritage Site (WHS) designation. Stakeholders such as the local community are often neglected or ignored and have derived very few benefits from tourism development of WHS in Malaysia. Thus, there is a dire need to evaluate the value of a cultural heritage in formulating heritage development plans making it physically, economically and socially acceptable as well as equally beneficial amongst the local stakeholders in order to preserve their cultural heritage sites, thus contributing towards the overall sustainable development of the WHS in Malaysia. The research adopts various approaches of study and triangulates the findings. The case study, Contingent Valuation questionnaire survey and interviews are the main strategies used for data collection. The single case study approach was carried out in search of empirical data on one of the historic cities in Malaysia i.e. George Town, Penang which has been recently inscribed as a UNESCO WHS. Three separate sets of questionnaires were designed and administered among the three key stakeholders in the field: local community, tourists and management personnel in the tourism and heritage site management. The Contingent Valuation is a direct Stated Preferences technique where respondents were asked their willingness-to-pay (WTP) value for the benefits received. The WTP value is one of the best techniques for estimating the total economic value of the cultural heritage resources that were not traded in the market. The public preferences, as measured by their WTP for the cultural heritage iv conservation, should be given due consideration in the decision-making process in order to promote the sustainability of a heritage site. This research has found that the George Town households were willing to pay RM57.46 per year and the tourist respondents were willing to pay RM42.54 per visit in the form of the conservation zone entry ticket or heritage building admission fee as a contribution for the George Town Heritage Conservation Fund. Both categories of respondents have shown their strong support for the George Town WHS conservation with the WTP value of the George Town WHS conservation. The managers also have shown their positive support for the proposed management of the WTP value of the cultural heritage for the sustainable George Town WHS conservation. Finally, this research has established a framework for the management of the WTP value of the cultural heritage for the sustainable George Town WHS conservation in Malaysia.